1992
DOI: 10.1080/02681219280000371
|View full text |Cite
|
Sign up to set email alerts
|

Immunoblotting analysis of sera from patients with candidal vaginitis and healthy females

Abstract: Antigenic components of Candida albicans were extracted from whole ceils with a buffer containing SDS and 2-mercaptoethanol, and separated by SDS-polyacrylamide gel electrophoresis. The components reactive with IgG, IgA, IgM and IgE antibodies in sera from patients with (14 subjects) and without (15 subjects) C. albicans in the vagina, and from healthy females (34 subjects), were investigated by immunoblotting using immunoglobulin class-specific antibodies. Many components reacted with IgG and IgA in all sera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
(16 reference statements)
2
13
0
Order By: Relevance
“…Tlie IgG4 detection showed reactivity in the high MW zone corresponding to C. albicans mannan. This is in accordance with previously published data (29) indicating that a short-term sensitizing antibody, probably IgG4, was elicited by mannans. It appeared that a vast array of C. albicans antigens elicits IgG3 production, but not production of the other subclasses, where reactive bands were fewer.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Tlie IgG4 detection showed reactivity in the high MW zone corresponding to C. albicans mannan. This is in accordance with previously published data (29) indicating that a short-term sensitizing antibody, probably IgG4, was elicited by mannans. It appeared that a vast array of C. albicans antigens elicits IgG3 production, but not production of the other subclasses, where reactive bands were fewer.…”
Section: Discussionsupporting
confidence: 94%
“…Shen et al (28) have identified a 40-kDa major allergen of C. albicans among asthmatic patients as an alcohol dehydrogenase. Ishiguro et al (29) identified various C. albicans allergens and purified three components (37, 43, and 46 kDa) from eytoplasmic fractions of C. albicans extract. Those tliree components appeared to be homologous to S. cerevisiae aldolase, phosphoglycerate kinase, and enolase, respectively The protein allergen described by Savolainen et al (25) had a MW of 46 kDa but represented a major allergen only in a pediatric asthmatic population.…”
Section: Discussionmentioning
confidence: 99%
“…3; number 15) were identified as PGK. This glycolytic enzyme has previously been characterised as an antigen that reacts with IgE antibodies present in sera from allergic patients [21].…”
Section: By Immunoblot Analysismentioning
confidence: 99%
“…Spot 19 showed homology to a C. albicans antigen that is reactive with an IgE antibody of sera from allergic patients [21]. This IgE-binding antigen is the glycolytic enzyme [8,9].…”
Section: Protein Identification By N-terminal Sequence Analysismentioning
confidence: 99%
“…The identification of glycolytic enzymes as immunogens during candidiasis is well documented. Thus, C. albicans enolase, phosphoglycerate kinase, alcohol dehydrogenase, pyruvate kinase, and aldolase have been described as major allergens/immunogens during candidiasis [7–16]. In addition, the presence of glycolytic enzymes on C. albicans cell wall is not unprecedented.…”
Section: Introductionmentioning
confidence: 99%